SEXUAL HEALTH EDUCATION: AN INTEGRATIVE REVIEW - Costa Duarte, Tamires; Claudino de Jesus Carvalho, Matheus; Regina Cesto Marques, Karla; dos Santos Silva, Ingrid; Henrique Abreu Belota, Luiz; Augusto Oliveira Teixeira, Frederico; Vieira Benevides Ferreira, Arthemis; Antonio Alves, Marcos; Regina Cesto Marques, Karla; José de Freitas Paciencia, Matheus; Bahú Machado, Liane; da Costa Araújo, Paulo (Health and Society, 2022)
Introduction: Health education is not just for teenagers, but it should be aimed at the target audience in general, only addressed at different times or occasions, because depending on age, each target has a specific method that must be discussed by professionals. Objective: To identify in the literature the strategies for carrying out the practice of sexual health education. Methodology: This study is an integrative literature review with a descriptive and exploratory approach, based on a survey of data in the scientific bases: BDENF, SCIELO and LILACS. Results and Discussions: By analyzing the studies selected by the literature, it is possible to highlight some important points regarding sexual education strategies. It is known that dialoguing with the subject demands good professional training, and therefore, knowledge and preparation becomes crucial for this process. The promotion of sexual and reproductive health is an issue that should be addressed to all audiences without age restrictions. Strategies for sex education in health are based on teaching, guiding and clarifying doubts about prejudices, taboos, sexually transmitted infections, contraceptive methods, doubts about changes in genital organs, female and male hormones, hygiene, self-care and among others. Conclusion: Based on the above, through this research, the need for health and education interventions with regard to sexuality and reproductive life is verified. The target audience should be broad, however, children and adolescents are prioritized as a priority for guidance on sex education.